Penerapan Metode Drill untuk Meningkatkan Kompetensi Siswa: Systematic Literature Review - Triani, Yeni (Yayasan Sembilan Pemuda Indonesia, 2025)
This research is a literature review that aims to analyze the application of the drill method in improving student competence. The drill method, which involves repeated practice, has been widely recognized as an effective technique in strengthening students’ understanding and skills in various subject areas. In this review, various studies identifying the positive impact of the drill method on improving students’ cognitive, affective and psychomotor abilities are reviewed. Based on the analysis, it was found that the application of the drill method can improve long-term memory, accelerate mastery of material, and increase accuracy and speed in completing tasks. However, the research also showed the importance of variation in the application of drill to avoid boredom and to maintain student motivation. The findings suggest that while the drill method is effective, its success is highly dependent on the teaching context, student engagement, as well as proper time management. Thus, the application of the drill method needs to be adapted to the characteristics of the students and the learning objectives to be achieved.